Pengaruh Kompensasi dan Pengembangan Karier Terhadap Komitmen Kerja (Studi kasus pada Karyawan Patra Jasa Convention Hotel Semarang) - Fitri Astuti Cahyaningtyas; Sudharto P Hadi (Universitas Diponegoro, 2017)
Low employee commitment causes negative effect to a company. With a low commitment, the employee is not dedicated, has the potential to make mistakes, disappoint customers and intending to leave the company. Work commitment of the employee in Patra Jasa Convention Hotel Semarang has fluctuated, it can be seen from the data of performance appraisal employee.This purpose of this study was to determine the effect of variable compensation and career development on the employees work commitment on Patra Jasa Convention Hotel Semarang. This type of research is explanatory research. The sample used 60 respondents who are permanent employees and contract employees. The sampling technique is simple random sampling. Methods of data analysis using correlation, simple linear regression, multiple linear regression, t test and f with IBM SPSS program 20. Based on the analysis, it can be concluded that the compensation and career development positively affects the work commitment through testing simple linear regression produce regression value of 0.969 and 0.776. The advice given to the company are to evaluate the compensation system and to provide greater career opportunities to employees, especially in providing promotions and job rotation.